CANTI POPOLARI LITUANI: THE FIRST COLLECTION OF LITHUANIAN FOLK POETRY IN ITALIAN - di Nuncio, Novella (Vertimo studijos, 2017)
The essay starts by analyzing an editorial project, the series Poesia popolare indoeuropea (Indo-European Folk Poetry), realized in Italy in 1930 under the guidance of the expert of Slavic Studies Ettore Lo Gatto. The series aimed at a vast audience, with the objective to inform and sensitize the society to ancient and folk literatures of the Indo-European area, a theme not so popular and almost unknown at that time, but also not easy to study, considering the historical period was closed to international cultures. Unfortunately, it was a short experience: the volumes composing the series were just three. The second one, Canti popolari lituani (Lithuanian Folk Songs) by Giuseppe Morici, is the first collection of Lithuanian dainos translated into Italian. This study places a special emphasis on Morici’s work, analyzing its contents and, through its example, reflecting on the issue of translation.